2006
DOI: 10.1111/j.1365-2982.2005.00748.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects and mechanisms of long‐pulse gastric electrical stimulation on canine gastric tone and accommodation

Abstract: Gastric electrical stimulation (GES) has been applied to treat gastroparesis and morbid obesity. The aims of this study were to evaluate the sites of stimulation and the mechanisms of GES on gastric tone and accommodation. Gastric tone and accommodation were evaluated with a barostat in surgically prepared dogs. GES was applied at seven different locations, and gastric tone was assessed at each site. The effect of truncal vagotomy on gastric tone and accommodation and the role of the nitrergic pathway were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 33 publications
1
52
0
Order By: Relevance
“…The orientation of the gastric cannula was marked during surgery, when the abdomen was open, to ensure accurate placement of the barostat bag into the fundus. The catheter was connected to a computer-controlled electrical barostat device (Distender Series IIR; G & J Electronics, Willowdale, ON, Canada) (57). After its placement in the fundus, the bag was briefly inflated with 300 ml air and then completely deflated.…”
Section: Measurement Of Gastric Tone and Accommodationmentioning
confidence: 99%
“…The orientation of the gastric cannula was marked during surgery, when the abdomen was open, to ensure accurate placement of the barostat bag into the fundus. The catheter was connected to a computer-controlled electrical barostat device (Distender Series IIR; G & J Electronics, Willowdale, ON, Canada) (57). After its placement in the fundus, the bag was briefly inflated with 300 ml air and then completely deflated.…”
Section: Measurement Of Gastric Tone and Accommodationmentioning
confidence: 99%
“…Literature has shown that GES using pulse trains or long pulses at a width >1 ms can affect gastric motility by causing changes in the gastric slow wave, antral contraction, and gastric emptying (7,9,10). Such stimulation is called inhibitory GES (iGES).…”
Section: Discussionmentioning
confidence: 99%
“…The pulsed train was on for a period of 2 s and off for 3 s, with an output current of 10 mA at a frequency of 40 Hz. The pulse width was increased every 2 min at an increment of 1 ms with the maximum width less than 20 ms (9). RGES or sham stimulation was performed.…”
Section: Retrograde Gastric Electrical Stimulationmentioning
confidence: 99%
“…1,5,7 Long-pulse GES is able to normalize gastric dysrhythmias, entrain gastric slow waves, accelerate gastric emptying, induce gastric relaxation, and inhibit rectal tone. 2,[6][7][8][9]16,[20][21][22][23] Long-pulse jejunal electrical stimulation is capable of accelerating intestinal transit in dogs and duodenum electrical stimulation is able to delay gastric emptying and reduce water intake in healthy humans. 11,17 CES with long pulses can significantly inhibit gastric tone and rectal tone.…”
mentioning
confidence: 99%